Harmony in Leadership: A Correlational Study between the Democratic Leadership Style of School Principals and the Integrity and Work Discipline of Teachers at SMA Negeri 4 Malang - Ratna Sukma Ningrum; Siti Awaliyah; Sri Untari (Journal of Educational Sciences, 2026)
This study investigated the relationship between the principal’s democratic leadership style and teachers’ integrity and work discipline at SMA Negeri 4 Malang. The study was motivated by the importance of effective school leadership in fostering teacher professionalism. A quantitative correlational design was applied, involving 62 teachers as respondents. Data were collected using Likert-scale questionnaires and analyzed through Pearson’s correlation with the Statistical Package for the Social Sciences. The results showed that the principal’s democratic leadership style, teacher integrity, and work discipline were all categorized as high, with percentages of 85%, 85%, and 86%, respectively. Statistical analysis indicated significant positive correlations between democratic leadership style and teacher integrity (r = 0.438; p < 0.01), and between democratic leadership style and work discipline (r = 0.329; p < 0.01). These findings demonstrate that democratic leadership contributes to strengthening teacher integrity and work discipline. Therefore, collaborative and participatory leadership is important for improving the quality of school management.